Hubungan Pengetahuan dan Sikap Ibu Balita dengan Perilaku Keluarga Sadar Gizi (KADARZI) - Devy Lestari Nurul Aulia; Arum Dwi Anjani (Journal for Quality in Women's Health, 2019)
Kadarzi Is a movement related to the family and Nutrition Health Program, which is part of the family nutrition Improvement Effort. Kadarzi, in other words, means family attitude and behavior can independently realize the best nutritional condition reflected inthe consumtion of diverse foodsnand quality balanced nutrition. The purpose of the study was tofind out whether there was a relationship between knowledge and attitudes of maothers of toddler under five with behaviors of Nutritional – concious Family (Kadarzi). The research design used in this study was the analytical survey method using the cross sectional approach. The population in this study were all mothers whi had toodlers age 1 – 5 years with total sample of 86 respondents, using purposive sampling technique.